The importance of multidisciplinary dating in rescue excavations: The case of Santhià, Northern Italy. (December 2019) - Tema, Evdokia; Ferrara, Enzo; Angelici, Debora; Fantino, Fulvio; Panero, Elisa
Highlights: A combined archaeomagnetic and thermoluminescence study on a baked clay kiln is presented. The results obtained from the two independent techniques are in significant agreement. The importance of such combined multidisciplinary investigation in the case of rescue excavations is highlighted. Abstract: We present the results of a combined archaeomagnetic and thermoluminescence (TL) investigation on a baked clay kiln discovered near Santhià, Northern Italy. The site, brought to light during a rescue excavation for the installation of methane tubes, provides important evidence for the presence of a brick production workshop in the area. Standard thermal demagnetization was applied to isolate the direction of the Characteristic Remanent Magnetization (ChRM). The mean ChRM direction was used for the archaeomagnetic dating of the kiln, suggesting that it was abandoned around the 16th century CE. TL analysis carried out on the same kiln further confirms this dating. The comparison between the archaeomagnetic and TL results shows excellent agreement, underlining the great potential of these two techniques in dating baked clays. Moreover, thanks to the independent TL dating, the new archaeomagnetic data can be used as a reference point for the reconstruction of the past secular variation path in Italy. Such combined multidisciplinary dating is extremely important in the case of rescue excavations, particularly in urban centers where the rapid expansion of new constructions inevitably causes the destruction of our cultural heritage and the loss of important information about our past.